(3QSGdI aj MH GdgQIs - (3Ydj Hf (B((3SdWGf(B) (3eMeO, fhQ GdOjf GdedG GdgQhj GdbGQj,J (B1014 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi MHH EdjfG GdEjeGf hcQg EdjfG GdcaQ hGdYUjGf hHYO ajbhd abO SCdfi Yf GdMOjK GdeTghQ Ydi CdSfI GdCYjGf MH GdgQI ef GdEjeGf (B" s
(3BNQgG (B:s
(3hbGd GdReNTQi dGjYQa ef jcQggg eef jHQg hai GdbGehS Ci eG jgQg eeG jHQg Ch GdbW ef GdaGQ Ch GdgQgQI ef GdHQjQI agPG GdPi SfM di ai gPG GdebGe hGddg CYde JeJ GdQSGdI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B23s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B12 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B100s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3eLGejY JjehQ (B136) s
Keywords: (3GdeLGejYs